A visual representation of microbiological culture data improves comprehension: a randomized controlled trial. (8th June 2021) - Kim, Eugene Y; Grossestreuer, Anne V; Safran, Charles; Nathanson, Larry A; Horng, Steven
Abstract: Objective: While the judicious use of antibiotics takes past microbiological culture results into consideration, this data's typical format in the electronic health record (EHR) may be unwieldy when incorporated into clinical decision-making. We hypothesize that a visual representation of sensitivities may aid in their comprehension. Materials and Methods: A prospective parallel unblinded randomized controlled trial was undertaken at an academic urban tertiary care center. Providers managing emergency department (ED) patients receiving antibiotics and having previous culture sensitivity testing were included. Providers were randomly selected to use standard EHR functionality or a visual representation of patients' past culture data as they answered questions about previous sensitivities. Concordance between provider responses and past cultures was assessed using the kappa statistic. Providers were surveyed about their decision-making and the usability of the tool using Likert scales. Results: 518 ED encounters were screened from 3/5/2018 to 9/30/18, with providers from 144 visits enrolled and analyzed in the intervention arm and 129 in the control arm. Providers using the visualization tool had a kappa of 0.69 (95% CI: 0.65–0.73) when asked about past culture results while the control group had a kappa of 0.16 (95% CI: 0.12–0.20). Providers using the tool expressed improved understanding of previous cultures and found the tool easy to use ( P < .001). Secondary outcomes showed no differences in prescribing practices. Conclusion: A visual representation of culture sensitivities improves comprehension when compared to standard text-based representations.